Bodies of Evidence: documentary photography and the black subject in the work of Carrie Mae Weems and Romare Bearden - Cobby, Rebecca (2006)
This dissertation considers the work of African American artists Carrie Mae Weems and Romare Bearden in relation to the difficulties inherent in representating the black subject in documentary photography. By taking images directly from institutional archives and media archives Weems and Bearden aim to reinterpret and reinvigorate the black subject through the processes of mixed media art. Documentary photography is inextricably linked to the configuration of the photographic process as an exact science which has led to its use in criminal and racial profiling. As such the black identity, when captured on film, has been defined solely through the racial classification and objectification of the body. Through processes of defamiliarisation, Weems and Bearden move beyond the physical to focus on the internal; on memory, African American culture and spirituality. How effective is this process in reinterpreting and reclaiming the black body? Are African Americans shielded from visual objectification in these works; or are they merely another form of appropriation?